Developing ESP supplementary reading exercises for second-year students at faculty of Nursing, Phu Tho Medical College = Xây dựng các bài tập đọc bổ trợ tiếng Anh chuyên ngành cho sinh viên năm thứ hai tại khoa Điều Dưỡng, trường Cao đẳng Y tế Phú Thọ. M. - Phan, Thị Thu Hà (University of Languages and International Studies, 2017)
40 p. + CD-ROM